Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Enseval Putera Megatrading cabang Pekanbaru menurut Perspektif Ekonomi Syariah - Syamsurizal, Syamsurizal (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
This research is motivated by the ups and downs in the quality of employee performance at PT Enseval Putera Megatrading Pekanbaru Branch from 2020 to 2022. Based on the formulation of the problems that have been made, this study aims to determine the effect of compensation and work environment on employee performance at PT Enseval Putera Megatrading Pekanbaru Branch This research is a type of quantitative research. The sample used in this study were employees of PT Enseval Putera Megatrading Pekanbaru Branch as many as approximately 52 people. Sampling technique by means of Simple Random Sampling. With data collection through observation, interviews, questionnaires and literature studies. The analysis technique in this study uses Multiple Linear Regression Analysis. This study uses multiple linear regression with the help of the SPSS Ver program. 21.00. The results of this study, compensation has a positive effect on employee performance. This is evident from the results of the t test which obtained t count X1 greater than t table, namely the value of t count (7.467) greater than t table (2.010) accepted at a significance level of 5%. The work environment has a positive effect on employee performance. This is evident from the results of the t test which obtained the t count X2 greater than the t table, namely the t value (7.484) greater than the t table (2.010), accepted at the 5% significance level. Compensation and work environment together have a positive effect on employee performance. This is evident from the results of the F test which shows the results of the F count of (415.672) greater than the F table of (3.19) accepted at the 5% significance level. Islamic economic review of the effect of compensation and work environment on employee performance at PT Enseval Putera Megatrading Pekanbaru branch can be categorized as sharia based on ijarah contract.